ANALISIS PEMBERDAYAAN MASYARAKAT PERSPEKTIF PEMERINTAHAN DAERAH - Windra Kurniawan (Politeknik Pembangunan Pertanian Bogor, 2020)
This research will elaborate the motivation of the community to participate in thesustainable development . In the village level in Bogor West Java, the activity of thedevelopment mainly dominate by the Head of the village (lurah) with all his followers. Howeverin the several village the participation of the community shows significant level, this can behappen because the community indicates they are willing to do something that may give thembenefits to the their village.This will give us understanding that the relationship between the institutions in thecommunityplay significant rules in the development, meanwhile the structure of the villageorganization also giving significant relations with the development.The resultshows that thestakeholders play main rule in the development, this happen if the village can be participate inthe development.